Defected graphite carbon catalyst and preparation method thereof

Through laminar premix reducing methane combustion technology, the equivalent ratio Φ is regulated, the combustion process is accurately controlled, and the defective graphite carbon catalyst is generated, which solves the problems of low efficiency in the construction of carbon materials and limited performance improvement in the existing technology, and achieves the preparation of efficient catalysts and the improvement of electrochemical performance.

CN119838589APending Publication Date: 2025-04-18HENAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510190437.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

When constructing defective carbon in carbon materials, the prior art has problems such as low construction efficiency, complex process, high cost, long synthesis time and limited performance improvement.

Method used

Laminar premixed reducing methane combustion technology is used to accurately control the H/O ratio and combustion temperature during the combustion process by regulating the equivalent ratio Φ, and introduce sp³ hybrid defect sites to generate defective graphite carbon catalyst.

Benefits of technology

Accurate control of defect sites of carbon materials is achieved, reducing operational complexity and cost, and significantly improving the preparation efficiency of catalysts and catalytic performance in electrochemical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838589A_ABST
    Figure CN119838589A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of carbon-based catalyst preparation, and particularly relates to a defective graphite carbon catalyst and a preparation method thereof. Comprising the following steps that methane and oxygen are input into a preheating area of a combustor to be mixed, and premixed gas is formed; conveying the premixed gas to a reaction zone of a combustor, and combusting to obtain a defective graphite carbon catalyst; in the premixed gas forming and combustion process, the H / O ratio and the combustion temperature of methane and oxygen in the premixed gas are controlled by regulating and controlling the equivalent ratio phi, and the equivalent ratio phi is 0.6-1.4. On the basis of a laminar premixing reductive methane combustion technology, introduction of defect sites of a carbon material and generation of a hybrid structure are realized by accurately controlling a combustion process, complex chemical reagents or extreme conditions are not needed, the operation complexity and cost are remarkably reduced, and preparation of an efficient catalyst is realized within a short time; and the catalytic performance in electrochemical applications such as oxygen reduction reaction and the like is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon-based catalyst preparation, and specifically relates to a defective graphite carbon catalyst and a preparation method thereof. Background Art

[0002] Carbon materials are widely used in many fields due to their excellent electrical, thermal and mechanical properties. However, the performance of carbon materials often depends on their internal structure and the distribution of defects. In the preparation of traditional graphite carbon materials, a high-temperature graphitization process is usually used. However, this process is energy-intensive and has harsh conditions, and it is difficult to control the precise generation of defects. Since the graphite layer formed at extremely high temperatures is highly ordered, how to induce the generation of disordered structures under appropriate energy input conditions has become a key technical challenge to improve the performance of carbon materials.

[0003] Existing technologies such as high-temperature heat treatment, plasma treatment and chemical doping have many shortcomings. First, these processes usually require extreme temperatures or complex chemical reagents, resulting in high energy consumption, high costs, and increased process complexity. Secondly, the generation of defects is difficult to accurately control, resulting in large fluctuations in the catalytic performance of the material and poor stability. In addition, some methods (such as laser treatment) are only suitable for small-scale experiments and are difficult to expand to industrial production. At the same time, these processes often destroy the crystal structure of the material, shorten the service life of the catalyst, and in some cases produce by-products that pollute the environment.

[0004] In summary, when constructing defective carbon in carbon materials using existing technologies, there are often problems such as low construction efficiency, complex process, high cost, long synthesis time and limited performance improvement. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a defective graphite carbon catalyst and a preparation method thereof. In order to overcome the problems of low construction efficiency, complex process, high cost, long synthesis time and limited performance improvement in the existing defective carbon materials, the present invention is based on laminar premixed reductive methane combustion technology, and proposes an innovative process for rapid preparation of carbon catalysts. By precisely controlling the combustion process, the technology realizes the introduction of defect sites in carbon materials and the generation of hybrid structures, without the need for complex chemical reagents or extreme conditions, significantly reducing the complexity and cost of operations, realizing the preparation of efficient catalysts in a short time, and greatly improving their catalytic performance in electrochemical applications such as oxygen reduction reactions.

[0006] The present invention solves the above technical problems through the following technical solutions.

[0007] The first object of the present invention is to provide a method for preparing a defective graphite carbon catalyst, comprising the following steps: Inputting methane and oxygen into the preheating zone of the burner for mixing to form a premixed gas; The premixed gas is transported to the reaction zone of the burner, and after combustion, sp³ hybrid defect sites are introduced into the graphite carbon layer by methane combustion to obtain a defective graphite carbon catalyst; During the formation of premixed gas and combustion, the H / O ratio of methane and oxygen in the premixed gas and the combustion temperature are controlled by adjusting the equivalent ratio Φ, and the sp in the graphite layer is broken by methane combustion. 2 bonds, thereby introducing sp³ hybridized defect sites into the graphite carbon layer, wherein the equivalent ratio Φ is 0.6 to 1.4.

[0008] Furthermore, the equivalent ratio Φ is 0.8 to 1.2.

[0009] Furthermore, when the equivalent ratio Φ is 0.8, the combustion temperature is 900°C to 930°C.

[0010] Furthermore, when the equivalent ratio Φ is 1.0, the combustion temperature is 950°C to 1000°C.

[0011] Furthermore, when the equivalent ratio Φ is 1.2, the combustion temperature is 950°C to 970°C.

[0012] The second object of the present invention is to provide a defective graphite carbon catalyst prepared by the above method.

[0013] Furthermore, the crystal structure of the defective graphite carbon catalyst is a semi-crystalline structure.

[0014] The third object of the present invention is to provide the use of the above-mentioned defective graphite carbon catalyst in electrocatalysis.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention aims to develop an innovative process based on laminar premixed methane combustion. By adjusting the single variable of the equivalent ratio Φ, the relationship between the H / O ratio, combustion temperature and propagation velocity is accurately controlled to ensure the efficient progress of the hydrogenation process and achieve precise control of defect generation to ensure that the reducibility and heat supply of the combustion process are optimally balanced. During the combustion process, the temperature is strictly controlled within a moderate range to prevent structural damage to the material due to excessively high temperature. By accurately controlling the combustion propagation velocity, the material is ensured to be heated evenly and local overheating is avoided, thereby improving the consistency of catalyst performance and preparation efficiency.

[0016] This technology is different from the traditional high-temperature oxidation method. It uses high-energy photons and heat generated by methane combustion at a lower temperature to quickly break the CC bonds in the graphite layer and promote the transformation from sp² to sp³ hybridization. The core lies in the coordinated control of hydrogenation and energy input: first, hydrogen radicals react with carbon atoms on the surface and edge of the carbon material to destroy the π bond structure and generate sp³ hybridization defects; second, the high-energy photons generated during the combustion process activate phonons through electron-phonon coupling, promote interlayer sliding and lattice reorganization, and achieve rapid optimization of catalytic materials. In addition, by regulating the equivalent ratio Φ, the relationship between H / O balance, temperature and propagation speed is optimized to ensure the efficient progress of the hydrogenation process. The present invention does not require complex chemical reagents or extreme conditions, significantly reduces the complexity and cost of operation, and avoids the degradation of material properties. It realizes efficient modification of carbon materials under mild conditions and the preparation of efficient catalysts in a short time, and greatly improves its catalytic performance in electrochemical applications such as oxygen reduction reactions, providing a new technical route for the development of high-performance carbon-based catalysts.

[0017] The present invention is the first to utilize methane combustion as both energy input and sp 3 -carbon generation pathway, achieving efficient modification of the surface and edges of carbon materials, which is different from traditional methods using plasma, laser or high-temperature heat treatment. The laminar premixed methane combustion technology ensures the controllability and stability of the combustion process, shortening the modification process from the traditional hours to seconds, greatly improving production efficiency. In addition, the process does not require high-energy equipment or chemical precursors, is compatible with existing industrial equipment, and reduces process complexity and cost. By reducing chemical waste and energy consumption, the present invention demonstrates excellent environmental advantages and provides a more sustainable process path for the preparation of carbon-based materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a mechanism diagram of the laminar premixed methane combustion process used in the present invention.

[0019] Figure 2 A schematic diagram of the combustion propagation process of a defective graphite carbon catalyst constructed for the present invention.

[0020] Figure 3 Infrared spectra of the defective graphite carbon catalyst and original graphite carbon constructed in Example 3 of the present invention.

[0021] Figure 4 Raman spectra of the defective graphite carbon catalyst and original graphite carbon constructed in Example 3 of the present invention.

[0022] Figure 5 The EDS spectrum and the full spectrum of the X-ray photoelectron spectroscopy of the defective graphite carbon catalyst and the original graphite carbon constructed in Example 3 of the present invention are shown in FIG. Figure 5In the figure, a is the EDS spectrum of AGC, b is the EDS spectrum of PGC, c is the corresponding EDS spectrum of a and b, and d is the full XPS spectrum.

[0023] Figure 6 X-ray photoelectron spectroscopy C 1s spectra of the defective graphite carbon catalyst and original graphite carbon constructed in Example 3 of the present invention.

[0024] Figure 7 The temperature distribution of the defective graphite carbon catalyst combustion process constructed in Examples 1 to 5 of the present invention, Figure 7 a in the figure is the temperature-resolved infrared image, and b is the relationship between the temperature of the core reaction area and Φ.

[0025] Figure 8 This is a Raman spectrum analysis diagram of the defective graphite carbon catalyst constructed in Examples 1 to 5 of the present invention, Figure 8 Where a is the Raman spectrum and b is the intensity ratio.

[0026] Fig. 9 The diagrams in the figure are a series of evolutionary process diagrams of the surface structure of the defective graphite carbon catalyst material constructed in Example 3 of the present invention transforming from PGC to AGC.

[0027] Fig.10 The structural characteristic diagram of the defective graphite carbon catalyst material and graphite carbon constructed in Example 3 of the present invention, Fig.10 Here, a is PGC and b is AGC.

[0028] Fig.11 The XPS spectra of the defective graphite carbon catalysts constructed in Examples 1 to 5 of the present invention are as follows: Fig.11 a in the figure is the XPS spectrum of PGC and AGC, and b is the summary of the intensity ratio of sp3 and sp2 peaks.

[0029] Fig.12 The XPS C KLL peak and d value diagram of the defective graphite carbon catalyst and graphite carbon constructed in Example 3 of the present invention, Fig.12 a is the XPS spectrum of C KLL, b is the smoothed version of the spectrum in a, c is the first-order derivative of b, and d is the d value derived from c.

[0030] Fig.13 This is a current-voltage curve diagram of a defective graphite carbon catalyst constructed in Example 3 of the present invention, Fig.13 a in FIG. 1 is the process of fitting the curve using the Butler-Volmer equation, b is the obtained Tafel curve, and the logarithmic value of j0 is calculated for each curve by fitting.

[0031] Fig.14 A comparison chart of the method for constructing a defective graphite carbon catalyst of the present invention and the prior art. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Existing technologies such as high-temperature heat treatment, plasma treatment and chemical doping often have problems such as low construction efficiency, complex process, high cost, long synthesis time and limited performance improvement when constructing defective carbon in carbon materials.

[0034] Based on the above problems, the present invention provides a method for preparing a defective graphite carbon catalyst, comprising the following steps: S1. Input methane and oxygen into the preheating zone of the burner for mixing to form a premixed gas. S2. The premixed gas is transported to the reaction zone of the burner, and after combustion, sp³ hybridized defect sites are introduced into the graphite carbon layer by using methane combustion to obtain a defective graphite carbon catalyst.

[0035] During the formation of premixed gas and combustion, the H / O ratio of methane and oxygen in the premixed gas and the combustion temperature are controlled by adjusting the equivalent ratio Φ, and the sp in the graphite layer is broken by methane combustion. 2 bonds, thereby introducing sp³ hybridized defect sites into the graphite carbon layer, wherein the equivalent ratio Φ is 0.6 to 1.4.

[0036] The present invention aims to develop an innovative process based on laminar premixed methane combustion. By adjusting the single variable of the equivalent ratio Φ, the relationship between the H / O ratio, combustion temperature and propagation velocity is accurately controlled to ensure the efficient progress of the hydrogenation process and achieve precise control of defect generation to ensure that the reducibility and heat supply of the combustion process are optimally balanced. During the combustion process, the temperature is strictly controlled within a moderate range to prevent structural damage to the material due to excessively high temperature. By accurately controlling the combustion propagation velocity, the material is ensured to be heated evenly and local overheating is avoided, thereby improving the consistency of catalyst performance and preparation efficiency.

[0037] It should be noted that the present invention adjusts the single variable of the equivalent ratio Φ, and the equivalent ratio Φ is a parameter used to describe the ratio of fuel to oxidant, which is defined as the ratio of the actual fuel to oxidant supplied to the stoichiometric ratio, reflecting the degree of deviation of the fuel and oxidant mixing state relative to the complete combustion or reaction conditions. If Φ=1, it means that the ratio of fuel to oxidant just meets the stoichiometric ratio, that is, theoretically there is no residual fuel or oxidant in the complete reaction; when Φ>1, it means that the fuel is excessive and the system is in a rich combustion state; and when Φ<1, the oxidant is excessive and the system is in a lean combustion state. Φ=(actual fuel / oxidant ratio) / (stoichiometric fuel / oxidant ratio). In the present invention, the regulation of Φ is based on the ratio of methane to oxygen.

[0038] This technology is different from the traditional high-temperature oxidation method. It uses methane combustion to introduce sp³ hybrid defect sites in the graphite carbon layer to obtain defective graphite carbon catalysts. More specifically, it uses high-energy photons and heat generated by methane combustion at a lower temperature to quickly break the CC bonds (sp² bonds) in the graphite layer and promote the transformation from sp² to sp³ hybridization. The core lies in the coordinated control of hydrogenation and energy input: first, during the combustion reaction of methane and oxygen, methane breaks bonds in the combustion reaction to form hydrogen radicals, which react with carbon atoms on the surface and edge of the carbon material to destroy the π bond structure and generate sp³ hybrid defects; secondly, the energy released by the reaction during the combustion process is expressed in the form of heat and light, and the high-energy photons generated by the deexcitation of excited molecules, free radical recombination and thermal radiation activate phonons through electron-phonon coupling, promote interlayer sliding and lattice reorganization, and achieve rapid optimization of catalytic materials. In addition, by regulating the equivalent ratio Φ, the relationship between H / O balance, temperature and propagation speed is optimized to ensure the efficient conduct of the hydrogenation process. The present invention does not require complex chemical reagents or extreme conditions, significantly reduces operational complexity and cost, and avoids the degradation of material properties. It achieves efficient modification of carbon materials under mild conditions and the preparation of efficient catalysts in a short period of time, and greatly improves their catalytic performance in electrochemical applications such as oxygen reduction reactions, providing a new technical route for the development of high-performance carbon-based catalysts.

[0039] Figure 1 FIG. 2 is a mechanism diagram of the laminar premixed methane combustion process of the present invention. Figure 1As shown, premixed reductive methane combustion (LPRMC) provides edge hydrogenation of surface carbon atoms and energy input for dislocation and rearrangement of carbon atoms. The energy input here mainly refers to heat, which is the driving force for structural deformation. At the same time, the large number of photons generated during the synthesis process cannot be completely ignored. Methane combustion mainly emits high-energy blue light. Visible photons drive structural deformation by increasing photoexcited carriers through electron interactions, which also selectively activates phonons through electron-phonon coupling, promoting rapid interlayer sliding. These changes in graphene stacking patterns can serve as intermediate steps, leading to sp 2 -sp 3 The formation of hybrid structure leads to sp 3 Although the effect of light may be very small due to low intensity, the synergistic effect of photoexcited electrons and the strain generated by hydrogenation may lower the energy threshold of heat, introduce edge hydrogenation and π bond breaking energy, and promote the formation of interlayer σ bonds, making it possible to achieve sp under such mild conditions on a time scale of seconds. 2 Possible key factors of deformation.

[0040] The present invention innovatively uses methane combustion as an energy source and a free radical generation pathway to achieve efficient modification of the surface and edge of carbon materials, which is different from the traditional methods of using plasma, laser or high-temperature heat treatment. Through the laminar premixed methane combustion technology, the controllability and stability of the combustion process are ensured, so that the modification process is shortened from the traditional hours to a few seconds, greatly improving the production efficiency. The present invention demonstrates excellent environmental advantages by reducing chemical waste and energy consumption, and provides a more sustainable process path for the preparation of carbon-based materials. In addition, the present invention achieves precise control of defects by regulating the equivalent ratio Φ and combustion parameters to ensure the stability and consistency of material properties. The process of the present invention does not require high-energy equipment or chemical reagents, can significantly reduce production costs and energy consumption, and has good environmental friendliness, suitable for large-scale industrial production. Through this innovative process, the present invention aims to provide a high-performance, long-life and low-cost carbon-based catalyst, providing a sustainable solution for applications in the field of electrochemistry.

[0041] In addition, the present invention also provides a defective graphite carbon catalyst prepared by the above method. The crystal structure of the defective graphite carbon catalyst is a semi-crystalline structure. The defective graphite carbon catalyst referred to in the present invention utilizes the heat energy, hydrogen radicals and high-energy photons generated by the combustion of methane to destroy its π bond structure and induce the formation of sp³ hybridization defects. These defect sites effectively improve the electrocatalytic performance of the carbon material, so that it exhibits better catalytic activity and selectivity in electrochemical applications such as oxygen reduction reactions. By adjusting the single variable of the equivalent ratio Φ, the relationship between the H / O ratio, the combustion temperature and the propagation speed is further optimized to ensure the efficient hydrogenation process and achieve precise control of defect generation. This systematic regulation enables the process to significantly improve the performance of the material while maintaining simplicity.

[0042] The invention is further described below through specific examples.

[0043] Example 1 A method for preparing a defective graphite carbon catalyst comprises the following steps: S1. Control the equivalent ratio Φ to 0.6, input methane and oxygen into the preheating zone of the burner for mixing to form a premixed gas.

[0044] S2. The premixed gas is transported to the reaction zone of the burner, and graphite material is added into the reaction zone. After combustion, the combustion temperature is controlled between 750°C and 820°C to ensure that the material is heated gently and avoid excessive defect generation, thereby obtaining a defective graphite carbon catalyst, named AGC.

[0045] Example 2 A method for preparing a defective graphite carbon catalyst comprises the following steps: S1. Control the equivalent ratio Φ to 0.8, input methane and oxygen into the preheating zone of the burner for mixing to form a premixed gas.

[0046] S2. The premixed gas is transported to the reaction zone of the burner, and graphite material is added into the reaction zone. After combustion, the combustion temperature is controlled between 900°C and 920°C to ensure that the material is heated gently and avoid excessive defect generation, thereby obtaining a defective graphite carbon catalyst, named AGC.

[0047] Example 3 A method for preparing a defective graphite carbon catalyst comprises the following steps: S1. Control the equivalent ratio Φ to 1.0, input methane and oxygen into the preheating zone of the burner for mixing to form a premixed gas.

[0048] S2. The premixed gas is transported to the reaction zone of the burner, and graphite material is added into the reaction zone. After combustion, the combustion temperature is controlled between 950°C and 1000°C to ensure that the material is heated gently and avoid excessive defect generation, thereby obtaining a defective graphite carbon catalyst, named AGC.

[0049] Example 4 A method for preparing a defective graphite carbon catalyst comprises the following steps: S1. Control the equivalent ratio Φ to 1.2, input methane and oxygen into the preheating zone of the burner for mixing to form a premixed gas.

[0050] S2. The premixed gas is transported to the reaction zone of the burner, and graphite material is added into the reaction zone. After combustion, the combustion temperature is controlled between 950°C and 970°C to ensure that the material is heated gently and avoid excessive defect generation, thereby obtaining a defective graphite carbon catalyst, named AGC.

[0051] Example 5 A method for preparing a defective graphite carbon catalyst comprises the following steps: S1. Control the equivalent ratio Φ to 1.4, input methane and oxygen into the preheating zone of the burner for mixing to form a premixed gas.

[0052] S2. The premixed gas is transported to the reaction zone of the burner, and graphite material is added into the reaction zone. After combustion, the combustion temperature is controlled between 930°C and 950°C to ensure that the material is heated gently and avoid excessive defect generation, thereby obtaining a defective graphite carbon catalyst, named AGC.

[0053] Comparative Example 1 Pristine graphitic carbon, named PGC.

[0054] The defective graphite carbon catalysts prepared in Examples 1 to 5 were tested for structure and performance, and the results are as follows: Figure 2 The schematic diagram of the combustion propagation process of defective graphite carbon catalyst constructed by the present invention is shown in FIG. Figure 2 As shown in Figure 2, the process can be controlled by the equivalent ratio Φ. The preheating zone and the reaction zone are distributed along the combustion propagation direction, and the preheating zone provides sufficient heat to promote the combustion reaction in the reaction zone.

[0055] Figure 3 The infrared spectra of the defective graphite carbon catalyst and the original graphite carbon constructed in Example 3 of the present invention are shown in FIG. Figure 3 As shown in the figure, there is a significant difference between the graphite carbon (AGC) treated by laminar premixed methane combustion and the original graphite carbon (PGC). The defective graphite carbon catalyst constructed in Example 3 has hydrogenated carbon atoms at 2000 cm -1 ~2300 cm-1 In this region, in addition to the conventional test noise, the AGC shows two significant CH absorption peaks, indicating that hydrogenation reaction occurs in the material during the combustion process.

[0056] Figure 4 The Raman spectra of the defective graphite carbon catalyst and the original graphite carbon constructed in Example 3 of the present invention are as follows: Figure 4 As shown in Figure 2, the ID / IG ratio of AGC is significantly higher than that of PGC, indicating that the number of defects in the material has increased after treatment. In addition, a more obvious D' peak appears in AGC, further proving the increase of surface defects in the material.

[0057] Figure 5 The EDS spectrum and the full spectrum of the X-ray photoelectron spectroscopy of the defective graphite carbon catalyst and the original graphite carbon constructed in Example 3 of the present invention are shown in FIG. Figure 5 a is the EDS spectrum of AGC, b is the EDS spectrum of PGC, c is the corresponding EDS spectrum of a and b, and d is the full XPS spectrum. Figure 5 As shown in a and b in the figure, the uniform distribution of carbon element is shown in Figure 5 As shown in Figures c and d, except carbon, there are no other elements such as oxygen or nitrogen, and no new elements or non-carbon functional groups (such as the commonly reported oxygen-containing functional groups) are introduced, proving that the system studied is a pure carbon system.

[0058] Figure 6 The X-ray photoelectron spectroscopy C 1s spectra of the defective graphite carbon catalyst and the original graphite carbon constructed in Example 3 of the present invention are shown in FIG. Figure 6 As shown, the C 1s peak further reveals the structural difference between PGC and AGC. In the XPS spectrum, the peak on the left represents the sp³ hybridized carbon content, and the peak on the right represents the sp² hybridized carbon content. The results show that compared with PGC, no new elements or non-carbon functional groups were introduced, and the proportion of sp³ hybridized carbon in AGC treated with laminar premixed methane combustion increased significantly, indicating that the material achieved a structural transformation from sp² to sp³ during the treatment process.

[0059] The LPRMC process is conducive to adjusting multiple key factors by adjusting a single variable equivalent ratio Φ. It affects sp in many ways 3Formation and regulation of catalytic performance: (1) The equivalent ratio Φ can easily control the combustion state to oxidation or reduction. By affecting the balance between H and O, the degree of oxidation of PGC and the amount of hydrogenation on the surface of PGC can be precisely adjusted. It should be noted that the value of the equivalent ratio Φ is calculated based on the synergy. Since the main material processed is carbon, there is a local fuel-rich condition. Therefore, the equivalent ratio Φ = 1 does not mean the stoichiometry of the entire system. Adjusting the value of the equivalent ratio Φ can very accurately control the oxygen content and achieve hydrogenation in a finely controlled manner. (2) The value of the equivalent ratio Φ directly affects the LPRMC propagation speed, which is a key combustion characteristic that determines the energy distribution on the carbon site and the amount of unburned hydrogen introduced into the PGC per unit time. The fastest propagation speed usually occurs between the equivalent ratio Φ values ​​of 1.0 and 1.2. (3) The equivalent ratio Φ value affects the shape and temperature of the LPRMC process, which in turn determines the efficiency of energy transfer to the PGC during combustion.

[0060] Figure 7 The temperature distribution of the defective graphite carbon catalyst combustion process constructed in Examples 1 to 5 of the present invention, Figure 7 a in the figure is the temperature-resolved infrared image, and b is the relationship between the temperature of the core reaction area and Φ. Figure 7 The figure shows the temperature distribution in different areas during laminar premixed methane combustion. The inserted number represents the equivalent ratio Φ, that is, the ratio of methane to oxygen. This parameter directly affects the state and temperature of combustion. The different colors in the image represent temperature changes. The brighter the color, the higher the temperature, corresponding to the specific temperature value marked in the color bar above. These images are used to ensure the uniformity of the combustion process and the precise control of temperature to prevent material damage and optimize defect introduction.

[0061] Figure 8 This is a Raman spectrum analysis diagram of the defective graphite carbon catalyst constructed in Examples 1 to 5 of the present invention, Figure 8 Where a is the Raman spectrum and b is the intensity ratio. Figure 8 As shown in a, the structures of PGC and AGC after treatment at different equivalent ratios Φ are compared. The spectra show characteristic peaks of D band, G band and D'' band. The D band reflects the defect density in the material, the G band corresponds to the ordered structure of the graphite layer, and the D'' band further reveals the change in defect type. The spectral changes under different equivalent ratio conditions show that the laminar premixed methane combustion process effectively changes the defect distribution on the surface and structure of the material; Figure 8 As shown in b, the intensity ratios between the D band, G band, and D'' band are extracted from the spectral data to describe the defect characteristics of the material under different processing conditions. These intensity ratios can reveal the degree of defect introduction and the structural optimization effect of the material, providing a reference for adjusting combustion parameters (such as the equivalent ratio Φ) to achieve optimal catalytic performance.

[0062] In the laminar premixed methane combustion process of the present invention, the microstructure of the carbon material is characterized by a double spherical aberration corrected transmission electron microscope to observe the structural change from PGC to modified AGC. Fig. 9 The diagram in FIG. 3 is a series of evolutionary diagrams of the surface structure of the defective graphite carbon catalyst material constructed in Example 3 of the present invention from PGC to AGC. Fig. 9 As shown, the order of changes is arranged in the numerical order shown in the figure, and the cross-sectional view of the TEM image with an interval of (0.34nm) shows that during this process, the crystal structure of the material gradually changes from a highly crystalline state to a quasi-crystalline state, and finally approaches an amorphous state, that is, a semi-crystalline structure, indicating that the crystal orderliness gradually disappears with the progress of the laminar premixed methane combustion process.

[0063] Fig.10 The structural characteristic diagram of the defective graphite carbon catalyst material and graphite carbon constructed in Example 3 of the present invention, Fig.10 a is PGC, b is AGC. Fig.10 As shown, the two show completely different structural characteristics. The SAED pattern of PGC has typical single crystal characteristics, indicating that its lattice arrangement is highly ordered. The SAED pattern of AGC shows polycrystalline characteristics, indicating that after laminar premixed methane combustion treatment, the structure of the material changes from an ordered single crystal state to a disordered polycrystalline state. This structural transformation effectively improves the electrocatalytic performance of the material by increasing the surface defects and active sites of the material, laying the foundation for its efficient performance in electrochemical applications such as oxygen reduction reactions.

[0064] Fig.11 The XPS spectra of the defective graphite carbon catalysts constructed in Examples 1 to 5 of the present invention are as follows: Fig.11 a is the XPS spectrum of PGC and AGC, b is sp 3 and sp 2 The intensity ratios of the peaks are summarized. Fig.11 As shown, the XPS electron energy spectra and sp 3 / sp 2 The change of carbon ratio reveals the influence of equivalent ratio Φ value on the chemical bond composition of carbon materials during combustion. Fig.11 As shown in a in Figure 2, with the increase of the equivalent ratio Φ, sp 3 The components gradually increase, especially when the equivalent ratio Φ=1.0~1.2, sp 3 The structure reaches the highest ratio; however, when the equivalent ratio Φ increases to 1.4, sp 3 The structure is reduced, which may be due to the partial reorganization or oxidation of the carbon structure caused by excessive combustion. Combined with the analysis of the above XPS peaks, the signal at 284.5 eV corresponds to C=C (sp2 structure), characterizing graphitized carbon, while the signal at 285.5 eV corresponds to CC (sp 3 structure), reflecting the hydrogenation or defect structure of the carbon surface. Fig.11 As shown in b, sp 3 / sp 2 The results show that in the range of equivalent ratio Φ=0.6~1.2, sp 3 / sp 2 The ratio increases with the increase of the equivalent ratio Φ, indicating that the appropriate equivalent ratio Φ value can promote sp 3 However, at the equivalent ratio Φ = 1.4, the ratio decreases due to the excess combustion leading to sp 3 The structure is further oxidized or regraphitized to sp 2 This indicates that the equivalent ratio Φ affects the structural rearrangement of carbon. When the equivalent ratio Φ is between 1.0 and 1.2, the oxidation / reduction balance is optimized, making sp 3 The structure reaches the highest proportions.

[0065] Fig.12 The XPS C KLL peak and d value diagram of the defective graphite carbon catalyst and graphite carbon constructed in Example 3 of the present invention, Fig.12 a is the XPS spectrum of C KLL, b is the smoothed version of the spectrum in a, c is the first-order derivative of b, and d is the d value derived from c. Fig.12 Figure 2 shows the C KLL Auger electron spectrum, where PGC and AGC are similar in overall trend, but there is a slight shift, which is consistent with the sp 2 / sp 3 The proportion of the structure is related to the change; in order to eliminate high-frequency noise, such as Fig.12 As shown in b, the data was smoothed to make the spectral curve clearer for further analysis; the first-order derivative processing was as follows Fig.12 As shown in c, it is used to highlight the extreme point of the Auger peak, so as to calculate the D-value, that is, the position offset of the maximum and minimum intensity peaks. The size of the D-value is related to the sp 2 / sp 3 Hybridization ratio is related, and higher D values ​​usually mean higher sp 2 content, while lower D values ​​indicate higher sp 3 Content. Fig.12 As shown in d, the D value and sp 2 The relationship between the content, where the X axis represents the D value and the Y axis represents the sp 2 The relative content of carbon is plotted for two reference materials, HOPG (highly ordered graphite, 100% sp 2) and diamond (100% sp 3 ), and mapped the data points of PGC and AGC to the curve. The results show that the D value of PGC is higher, which means that it is still sp 2 The D value of AGC is reduced, indicating that it has a higher sp 3 content, indicating that the combustion treatment resulted in sp 2 →sp 3 This further verifies that the regulation of the equivalent ratio Φ has a direct effect on the electronic structure of the carbon catalyst during LPRMC (laminar premixed reducing methane combustion). The above shows that the oxidation / reduction environment during the combustion process can effectively regulate the sp 3 Formation, and maximize sp under appropriate combustion conditions (equivalent ratio Φ = 1.0 ~ 1.2) 3 structural content, while excessive combustion (equivalence ratio Φ>1.4) may lead to sp 3 Re-graphitization of the structure.

[0066] The Butler-Volmer principle is used to fit the current-voltage (JV) curve to obtain the exchange current density (jo) of the material. Fig.13 This is a current-voltage curve diagram of a defective graphite carbon catalyst constructed in Example 3 of the present invention, Fig.13 Where a is the process of fitting the curve using the Butler-Volmer equation, b is the obtained Tafel curve, and the logarithmic value of j0 is calculated for each curve by fitting. Fig.13 As shown in a, by taking the logarithm of the current density of the original JV curve and extrapolating it to the current axis, the intersection with the current axis is the exchange current density j0. This process is used to quantify the intrinsic activity of the electrode at zero potential and is an important indicator for judging the performance of the catalyst. Fig.12 As shown in (b), the obtained Tafel curves are fitted to calculate the logarithmic value of j0 for each curve. It should be noted that in order to be consistent with the conventional display format, the image in this part has the directions of the x-axis and y-axis interchanged with the schematic diagram in (a). These Tafel curves are used to evaluate the electrochemical performance of materials under different treatment conditions. The higher the j0 value, the stronger the intrinsic catalytic activity of the material. By fitting and analyzing the Tafel curves, the present invention can systematically optimize the electrocatalytic performance of the material.

[0067] Fig.14 The method for constructing defective graphite carbon catalyst of the present invention is compared with the prior art, such as Fig.14 As shown, Fig.14The data in represent references, as shown in Table 1, covering different electrochemical test conditions, and different geometries represent a variety of methods for carbon material modification. From the clustered areas of each method in the figure, we can roughly observe the performance range and processing time required for each method. The ideal treatment method is located in the upper left corner of the figure, indicating the shortest processing time and the greatest performance improvement. The laminar premixed methane combustion process used in this study is marked as a snowflake in the figure, located in the upper left corner, which shows that this method not only significantly reduces the overpotential of the catalyst, but also completes the modification of the material in a very short time, showing the superiority of high efficiency and short processing cycle.

[0068] Table 1 Fig.13 The data in this article represent references In summary, the present invention realizes the rapid and efficient synthesis of carbon materials, completes the modification within seconds, generates highly active carbon materials rich in sp³ hybrid defects, greatly improves their electrocatalytic performance, and exhibits higher current density, lower overpotential and excellent Faraday efficiency in oxygen reduction reaction, fuel cell and water electrolysis systems. The present invention provides an efficient and low-cost technical path for clean energy and environmental governance.

[0069] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0070] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a defective graphite carbon catalyst, characterized in that: The following steps are involved: Inputting methane and oxygen into the preheating zone of the burner for mixing to form a premixed gas; The premixed gas is transported to the reaction zone of the burner, and after combustion, sp³ hybrid defect sites are introduced into the graphite carbon layer by methane combustion to obtain a defective graphite carbon catalyst; During the formation of premixed gas and combustion, the H / O ratio of methane and oxygen in the premixed gas and the combustion temperature are controlled by adjusting the equivalent ratio Φ, and the sp in the graphite layer is broken by methane combustion. 2 bonds, thereby introducing sp³ hybridized defect sites into the graphite carbon layer, wherein the equivalent ratio Φ is 0.6 to 1.

4.

2. The method for preparing a defective graphite carbon catalyst according to claim 1, characterized in that: The equivalent ratio Φ is 0.8~1.

2.

3. The method for preparing a defective graphite carbon catalyst according to claim 2, characterized in that: When the equivalent ratio Φ is 0.8, the combustion temperature is 900 ℃ ~ 930 ℃.

4. The method for preparing a defective graphite carbon catalyst according to claim 2, characterized in that: When the equivalent ratio Φ is 1.0, the combustion temperature is 950 ℃ ~ 1000 ℃.

5. The method for preparing a defective graphite carbon catalyst according to claim 2, characterized in that: When the equivalent ratio Φ is 1.2, the combustion temperature is 950 ℃ ~ 970 ℃.

6. A defective graphite carbon catalyst, characterized in that The method is prepared by any one of claims 1 to 5.

7. The defective graphite carbon catalyst according to claim 6, characterized in that The crystal structure of the defective graphite carbon catalyst is a semi-crystalline structure.

8. Use of the defective graphite carbon catalyst according to claim 6 in electrocatalysis.